Some Economic Considerations for Composite Floor Beams - Lorenz, Robert F. (Engineering Journal, 1983)
To the discerning structural engineer, changes in specification rules always offer an economic opportunity to find new and better ways to implement savings in material or labor costs. In a subtle manner, a 1978 AISC Specification rule change for partial composite design of steel flexural members strongly improved the opportunity to make important economic savings in optimizing the floor system costs. The change was simply the introduction of a squareroot power instead of a linear relationship in Specification Eq. (1.11).